Attitudes and use of complementary and alternative medicine: a cross-sectional comparison between medical and non-medical students - Zakeri, Maryam; Dehghan, Mahlagha; Soltanmoradi, Yaser; Monfared, Shiva; Kose, Gulsah; Farahmandnia, Hojjat; Hermis, Alaa Hamza; Xu, Xiao; Zakeri, Mohammad Ali (Frontiers in Pharmacology, 2025)
Students are one of the groups in society that use complementary and alternative medicine (CAM). Given their role in promoting the use of CAM and the potential differences in attitudes due to their educational backgrounds, it is important to investigate their perspectives on CAM. This study aimed to compare the attitudes and use of CAM between medical and non-medical students. The study employed a cross-sectional design and was conducted among 525 medical and non-medical students in Iran. Data were collected using a descriptive information form, a CAM questionnaire, and the Holistic Complementary and Alternative Medicine Questionnaire (HCAMQ). The data were analyzed using SPSS version 25. The mean HCAMQ scores for medical and non-medical students were 33.10 ± 5.39 and 31.96 ± 5.48, respectively. A significant difference was found between medical and non-medical students in terms of their attitudes toward CAM, as measured by the HCAMQ subscale (p = 0.005). Additionally, 72.8% of medical students and 61.0% of non-medical students reported using at least one CAM method. A positive and statistically significant relationship was observed between medical and non-medical students in terms of their overall use of CAM (p = 0.005) and nutritional supplement methods (p = 0.025). Analysis of the reasons for using CAM revealed that only the use of medicinal herbs showed a significant difference between medical and non-medical students (p = 0.002). Finally, there was no statistically significant difference between the two groups in terms of consulting a physician before using CAM methods. Given the significant difference in attitudes toward CAM between medical and non-medical students, it is essential to address the distinct educational needs of these two groups. Developing effective and targeted educational programs could improve their knowledge and promote the safe and informed use of CAM.